Traditional agricultural tools and implements used in Wokha, Nagaland - Singh, L Kanta; Devi, S. Roma; Singh, Meitram Hemerjit (Indian Journal of Hill Farming, 2015)
Wokha district has population of 166,343 with geographical area of 1628 sq. km and main occupation of the people in the district is cultivation. People in the district mainly depend on shifting cultivation or Jhum but horticulture plantation and other non-agricultural resources are also being practiced at minor scale. Jhum cultivation has been devised over generations through the innate experience and knowledge gained by the rural people over the land, labour, environment resources available and the cropping requirements. Average annual area under Jhum cultivation of Wokha district is 13900 ha and total area under agricultural crops in the district ranges from 38680 ha to 48150 ha. Traditional tools and implements dominated over the modern equipments in all agricultural activities in Wokha district. About 93842 agricultural farmers out of total population involved in all the agricultural activities in the district. Because of the geographical condition like steep slope, small terrace size, undulating terrain, etc. area is not suitable for modern power and machinery and the only alternatives left to solve such problems are through traditional tools and implements. Traditional tools and implements are locally developed and cost of manufacturing is less due to use of locally available raw materials and these implements and tools may be further improved through local artesian and famers for achieving self-reliant in the district.